High-intensity Focused Ultrasound Treatment in Moderate Glaucoma Patients: Results of a 2-Year Prospective Clinical Trial - Leshno, Ari; Rubinstein, Yair; Singer, Reut; Sher, Ifat; Rotenstreich, Ygal; Melamed, Shlomo; Skaat, Alon (Journal of glaucoma, 2020)
Ultrasound Cyclo Plasty (UCP) treatment using high-intensity focused ultrasound (HIFU) is an effective and safe therapy to reduce intraocular pressure (IOP) in moderate glaucoma patients as was measured during a 2-year follow-up period. The purpose of this study was to evaluate the long-term safety and efficacy of the UCP procedure using HIFU in moderate glaucoma patients. A prospective interventional noncomparative study was carried out. Fifteen patients (15 eyes) with moderate open-angle glaucoma were enrolled. All eyes were treated with UCP-HIFU. A thorough ophthalmic examination and IOP measurements were performed before the UCP-HIFU procedure and at 1 day, 1 week, 4 weeks, 3 months, 6 months, 1 year, and 2 years after the procedure. The primary outcome was defined as a surgical success (IOP reduction of 20% or ≥5 mm Hg) at the last follow-up visit. The secondary outcomes were the mean IOP at each follow-up visit, number of medications used, complications profile, and reinterventions. The mean preoperative IOP at baseline was 26.8±5.0 mm Hg. All patients had a positive response and a lower IOP after treatment, with a relatively stable 31% reduction in IOP during the follow-up period. A significant reduction in IOP was observed at all postprocedure examination points (P<0.01), with a mean 17.6±4.4 mm Hg at 2 years after the procedure (P=0.005). Surgical success was achieved in 87% of the patients at their last follow-up visit. There was a nonsignificant decrease in the mean number of glaucoma medications from 2.5±0.8 to 2.0±1.0 at 2 years (P=0.48). No major intraoperative or postoperative complications were noted. UCP-HIFU treatment is an effective, safe, and well-tolerated method to reduce IOP in patients with moderate glaucoma.